Genome-wide association study of asthma identifies RAD50-IL13 and HLA-DR/DQ regions - Li, Xingnan; Howard, Timothy D.; Zheng, Siqun L.; Haselkorn, Tmirah; Peters, Stephen P.; Meyers, Deborah A.; Bleecker, Eugene R. (Journal of allergy and clinical immunology, 2010)
Asthma is a heterogeneous disease that is caused by the interaction of genetic susceptibility with environmental influences. Genome-wide association studies (GWASs) represent a powerful approach to investigate the association of DNA variants with disease susceptibility. To date, few GWASs for asthma have been reported. A GWAS was performed on a population of patients with severe or difficult-to-treat asthma to identify genes that are involved in the pathogenesis of asthma. A total of 292,443 single nucleotide polymorphisms (SNPs) were tested for association with asthma in 473 The Epidemiology and Natural History of Asthma: Outcomes and Treatment Regimens (TENOR) cases and 1892 Illumina general population controls. Asthma-related quantitative traits (total serum IgE, FEV 1, forced vital capacity, and FEV 1/forced vital capacity) were also tested in identified candidate regions in 473 TENOR cases and 363 phenotyped controls without a history of asthma to analyze GWAS results further. Imputation was performed in identified candidate regions for analysis with denser SNP coverage. Multiple SNPs in the RAD50-IL13 region on chromosome 5q31.1 were associated with asthma: rs2244012 in intron 2 of RAD50 ( P = 3.04E-07). The HLA-DR/DQ region on chromosome 6p21.3 was also associated with asthma: rs1063355 in the 3′ untranslated region of HLA-DQB1 ( P = 9.55E-06). Imputation identified several significant SNPs in the T H2 locus control region 3′ of RAD50. Imputation also identified a more significant SNP, rs3998159 ( P = 1.45E-06), between HLA-DQB1 and HLA-DQA2. This GWAS confirmed the important role of T H2 cytokine and antigen presentation genes in asthma at a genome-wide level and the importance of additional investigation of these 2 regions to delineate their structural complexity and biologic function in the development of asthma.